Estratégias de prevenção e atenção acriança e o adolescente vítimas da violência escolar - Anunciação, Leilane Lacerda (2018)
The history of violence against children and adolescents, traverses the trajectory of human evolution. Considered a phenomenon due to its size, it requires an expanded view, since it is a complex, multifaceted, multifactorial problem, perpetrated in all societies, in the intra and extra family environment, it is associated with a relation of power over the child and the adolescent. School violence, whether in physical, symbolic or verbal form, has reached unprecedented proportions, becoming a complex and difficult world phenomenon, with serious repercussions for its victims. The importance of health in the protection network is emphasized, with innovative actions to break the cycle of violence, since this is already a public health problem, due to the dizzying growth of its occurrence and the increase of morbidity and mortality rates in this age group. Therefore, we propose with this study a multidisciplinary intervention for prevention, attention and follow-up of the victims of school violence, with the general objective of constructing proposals for prevention and attention to school violence for the constitution of territories of peace, together with school community of the Public School Valdemira Alves de Brito, ESF SítioMatias and NASF XVI, in Feira de Santana - Bahia; and specific objectives: To analyze the conceptions of school violence for the professionals of the ESF SítioMatias, NASF XVI team and school community, of the Public School Valdemira Alves de Brito; To implement training of health and education professionals in the SítioMatias neighborhood, as a pilot project, articulated to the PublicIntersectorial Work Group (GTI-M) of the Health in the School Program, regarding prevention and attention of violence in the school environment; Develop together with ESF / NASF, school community and public power, strategies for the prevention, reduction and attention to school violence and a culture of peace, at the Public School Valdemira Alves de Brito. It is a study with a qualitative approach, having as a design, action research, being a descriptive, exploratory research. The participants were the school community and ESF / NASF professionals from that neighborhood. The primary data were collected through systematic observation and semi-structured interviews, from July to December 2017. The wheels of conversations and seminars were used as tools for situational diagnosis, conflict mediation and to develop planned interventions. Secondary data were collected through bibliographies on the topic published in the last ten years, consultation of previous results of research related to NIEVS / UEFS and institutional documents of the Ministry of Health and the Secretariats of Health and Education of de city. The data generated were analyzed using the content analysis method. The results of this study ratified the fact that the school is a scenario where children and adolescents are victims of violence. We identified that school violence is manifested in multiple ways, requires multidisciplinary and intersectoral interventions, qualified. The exchange of knowledge was very beneficial, rewarding and resulted in very positive repercussions for the prevention and attention to situations of violence in the context of that school, despite the varied social, cultural and economic implications that individuals are immersed. Intervention practices, which prioritized educational actions by a problematic, horizontal and interdisciplinary logic, facilitated the achievement of good results. As products originating from this study, we can highlight: strengthening the link between professionals working in the local service network who envisage intervening in this problem; workshops and activities playful, implementation of the project of physical activity in the school; proposition of a new model of mediation of conflicts in the school environment; approaching the family to school; intersectoral project for the qualification of health professionals and education for the prevention and attention to violence and elaboration of an instructive primer for professionals. The other data from the research will be explored in other productions